KAJIAN PENGELOLAAN SAMPAH BERBASIS EKONOMI MASYARAKAT DENGAN KONSEP 3R DI KABUPATEN KOLAKA - Kabupaten Kolaka, Balitbang; Sofian Maksar, Muhammad; Lapau, Fitria; Ndibale, Wa (JIDE : Journal Of International Development Economics, 2025)
This study aims to examine community-based waste management using the Reduce, Reuse, and Recycle (3R) approach in Kolaka Regency. The increasingly complex waste problem negatively impacts the environment and health, and demonstrates the need for active community involvement in its management. This study emphasizes the importance of community empowerment, especially women, as driving agents in processing household waste that has economic value. Through a descriptive qualitative approach using interview, observation, and documentation methods, this study found that the application of the 3R concept has great potential to be integrated into sustainable development strategies in Kolaka. Although there are still limitations in infrastructure and community knowledge, the results of the study indicate that with the support of appropriate policies, education, and cross-sector partnerships, community-based waste management can be an effective solution that not only reduces waste generation but also encourages local economic growth.